2020
DOI: 10.3390/cancers12102961
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Complications in Patients with Hepatocellular Carcinoma Treated with Sorafenib

Abstract: VEGF(R)-targeted therapies are associated with an increased risk of thromboembolism and bleeding, which might be pronounced in patients with increased cardiovascular risk. Nevertheless, sorafenib represents an important treatment option in patients with hepatocellular carcinoma (HCC). We retrospectively investigated the risk of arterial/venous thromboembolic and bleeding events in 252 patients treated with sorafenib for HCC between 05/2006 and 03/2020 at the Medical University of Vienna. Cardiovascular risk wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
1
10
1
Order By: Relevance
“…While bleeding episodes in this population may be related to a DOAC-associated haemostatic failure, it cannot be excluded that these bleedings were triggered by other risk factors such as portal hypertension 19 or tyrosine kinase inhibitor therapy. 35 While no baseline or laboratory parameter was predictive of spontaneous bleeding in the US study, 18 we did observe an association of spontaneous bleeding with liver function. However, it is unclear whether the observed increased bleeding risk simply reflects the more fragile haemostatic balance in patients with more pronounced liver dysfunction or is caused by DOAC treatment.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…While bleeding episodes in this population may be related to a DOAC-associated haemostatic failure, it cannot be excluded that these bleedings were triggered by other risk factors such as portal hypertension 19 or tyrosine kinase inhibitor therapy. 35 While no baseline or laboratory parameter was predictive of spontaneous bleeding in the US study, 18 we did observe an association of spontaneous bleeding with liver function. However, it is unclear whether the observed increased bleeding risk simply reflects the more fragile haemostatic balance in patients with more pronounced liver dysfunction or is caused by DOAC treatment.…”
Section: Discussioncontrasting
confidence: 51%
“…Importantly, we observed that CPS‐B/C patients receiving DOAC had a significantly higher risk for spontaneous bleeding when compared with patients with CPS‐A cirrhosis. While bleeding episodes in this population may be related to a DOAC‐associated haemostatic failure, it cannot be excluded that these bleedings were triggered by other risk factors such as portal hypertension 19 or tyrosine kinase inhibitor therapy 35 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…3,4 Nonetheless, other important cardiovascular toxicities (including myocardial ischemia, QT prolongation, cerebrovascular accidents (CVA) or vascular peripheral ischemia) do not seem to have been highlighted during drug development or the pivotal randomised controlled trials for regulatory approval, due to its apparently low incidence. 2,5,6 To date, only a few clinical studies have focused on the cardiovascular complications in actual clinical practise. Moreover, most clinical information available comes from renal studies, 7 with a different clinical profile of patients than those affected by HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Sorafenib (SOR) is a multitarget TKI, 2 mainly used for the treatment of advanced hepatocellular carcinoma (HCC) and renal cell carcinoma. Although SOR significantly prolongs patients' overall survival (OS), its use is associated with different adverse events (AEs), mainly dermatological and gastrointestinal but also cardiovascular, especially high blood pressure (BP) 3,4 .…”
Section: Introductionmentioning
confidence: 99%